Establishment and characterization of Drosophila cell lines mutant for heparan sulfate modifying enzymes. (24th April 2019) - Nakato, Eriko; Liu, Xin; Eriksson, Inger; Yamamoto, Maki; Kinoshita-Toyoda, Akiko; Toyoda, Hidenao; Kjellén, Lena; Li, Jin-ping; Nakato, Hiroshi
Abstract: A class of carbohydrate-modified proteins, heparan sulfate proteoglycans (HSPGs), play critical roles both in normal development and during disease. Genetic studies using a model organism, Drosophila, have been contributing to understanding the in vivo functions of HSPGs. Despite the many strengths of the Drosophila model for in vivo studies, biochemical analysis of Drosophila HS is somewhat limited, mainly due to the insufficient amount of the material obtained from the animal. To overcome this obstacle, we generated mutant cell lines for four HS modifying enzymes that are critical for the formation of ligand binding sites on HS, Hsepi, Hs2st, Hs6st and Sulf1, using a recently established method. Morphological and immunological analyses of the established lines suggest that they are spindle-shaped cells of mesodermal origin. The disaccharide profiles of HS from these cell lines showed characteristics of lack of each enzyme as well as compensatory modifications by other enzymes. Metabolic radiolabeling of HS allowed us to assess chain length and net charge of the total population of HS in wild-type and Hsepi mutant cell lines. We found that Drosophila HS chains are significantly shorter than those from mammalian cells. BMP signaling assay using Hs6st cells indicates that molecular phenotypes of these cell lines are consistent with previously known in vivo phenomena. The established cell lines will provide us with a direct link between detailed structural information of Drosophila HS and a wealth of knowledge on biological phenotypic data obtained over the last two decades using this animal model.